Regional Investment, Fiscal Transfers, and Local Revenues: An Analysis of Working Capital Lending by Regional Development Banks in Indonesia - Aswan, Andi; Jusni, Jusni; Dewi, Andi Ratna Sari; Agusalim, Muhammad (International Journal of Economics and Financial Issues, 2025)
This study explores the influence of fiscal and macroeconomic factors on working capital loan allocation by Regional Development Banks (RDBs) in Indonesia, with particular attention to how regional investment, government transfers, and economic growth contribute to credit distribution at the provincial level. The research employs multiple regression analysis on 180 panel data observations from 16 RDBs, using secondary data collected from regional financial statistics and annual RDB reports spanning the period 2013–2021. Eight explanatory variables are examined: domestic investment, foreign direct investment (FDI), general allocation funds (DAU), special allocation funds (DAK), local retributions, local taxes, proceeds from the management of separated regional assets, and provincial economic growth. The findings reveal that DAU has a statistically significant negative effect on credit disbursement, suggesting that high fiscal dependency may weaken financial autonomy and reduce the perceived creditworthiness of borrowing regions. Conversely, revenue from separated regional assets exhibits a strong positive impact, highlighting the role of productive asset management in enhancing access to credit. While both domestic and foreign investment show positive coefficients, their effects are statistically insignificant, possibly due to concentration in capital-intensive sectors with limited direct impact on micro, small, and medium enterprises (MSMEs). Local taxes exert a significant negative influence, whereas local retribution and provincial economic growth do not significantly affect lending behavior. The results underline the importance of fiscal structure, financial independence, and institutional governance in shaping regional credit markets. Policy efforts aimed at improving local asset productivity and reducing dependency on central transfers are essential to strengthen regional financial ecosystems and promote inclusive economic development. These findings contribute to broader policy discussions on fiscal decentralization and subnational financing within emerging economies.